TAFSIR PERNIKAHAN BEDA AGAMA: KAJIAN PERBANDINGAN DAN KRITIK - Achmad Yaman (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2024)
The book Interfaith Fiqh: Building an Inclusive-Pluralist Society is one of the books published by the Paramadina Foundation in collaboration with The Asia Foundation. This research aims to show any irregularities or irregularities in the interpretation of the Koran by the authors, especially sensitive matters and principles in Islamic Sharia. This research method uses a critical comparative study method of the authors' interpretations in explaining interfaith marriages. The authors use a new interpretive approach, according to them, which is known as the Hermeneutic Method, namely a method that is contextual and interprets everything, including the Koran, in a liberal, free way and even seems haphazard without maintaining the sanctity of the Islamic holy book. Based on the research results, it can be concluded that the authors' interpretation of Interfaith Marriage using a Hermeneutic approach is not in accordance with mainstream Islamic teachings or the interpretive methodology of ulama whose knowledge and understanding of the Koran is beyond doubt.